Long-term adverse effects of benzodiazepine use (Research, Society and Development, 2022)
Benzodiazepines (BZD) are drugs whose main clinical indications are associated with anxiety, insomnia, muscle relaxation, relief of spasticity caused by central nervous system pathology, and epilepsy. The main adverse effects related to long-term use of BZD are memory loss, decline in cognitive function, imbalance, and reduced judgment. This is an integrative review based on searches of the SCIELO, PUBMED, and VHL databases, using the following inclusion criteria: articles published in the last 5 years, free full text, answering the guiding question, and written in English, Portuguese, or Spanish. For the review, 10 articles were selected and analyzed according to the pattern of the most common adverse effects, which are: suicidal and self-injurious behavior, delirium, overdoses, paralytic ileus, myopathies, triglyceride elevation, and ocular signs and symptoms. The profile of patients in long-term BZD use is female, with low education and greater clinical impairments. Furthermore, an association between chronic BZD use and hippocampal atrophy, representing the pattern of Alzheimer's disease, has been reported; however, a direct relationship cannot be stated. Since there is suspicion of neurodegeneration associated with the use of BZD, it is necessary to follow up with new studies in order to generate better quality of life, guaranteeing integral health care and preventing the aggravations related to the prolonged use of this medication.